Antibiotic use as a marker of acute infection and risk of first and recurrent venous thrombosis. (17th February 2017) - Timp, Jasmijn F.; Cannegieter, Suzanne C.; Tichelaar, Vladimir; Braekkan, Sigrid K.; Rosendaal, Frits R.; le Cessie, Saskia; Lijfering, Willem M.
Summary: A role for transient infections in the aetiology of venous thrombosis (VT) has been suggested. This study aimed to determine whether individuals who receive antibiotic treatment (as a proxy for infections) have an increased risk of first and recurrent VT and whether infections should be seen as a provoking risk factor for VT. We used the self‐controlled case series method to study the risk of first VT during antibiotic prescriptions. The risk of recurrent VT during antibiotic use was estimated by of time‐dependent Cox‐regression. A total of 2547 patients with a first VT were included and followed for a median of 5·9 years for recurrence (1999–2010), in whom 114 first events occurred during antibiotic use. We found a five‐fold increased risk of first VT during antibiotic treatment: [incidence‐rate‐ratio 5·0; 95% confidence interval (CI), 4·0–6·1]. Antibiotic use was associated with a 2·0‐fold (95% CI, 1·1–4·0) increased risk of recurrent VT. Patients with an unprovoked first VT who used antibiotics shortly before this event, had a similar risk of recurrence as patients with a provoked first VT (adjusted hazard ratio 1·1; 95% CI, 0·7–1·7). Individuals who receive antibiotics have an increased risk of first and recurrent VT and infections should be considered a provoking risk factor for VT.